The Battle Over Patents History and the Politics of Innovation - Haber, Stephen H. 1957-; Lamoreaux, Naomi R. 1950- (National Bureau of Economic Research, 2021)
This essay is the introduction to a book of the same title, forthcoming in summer of 2021 from Oxford University Press. The purpose is to document the ways in which patent systems are products of battles over the economic surplus from innovation. The features of these systems take shape as interests at different points in the production chain seek advantage in any way they can, and consequently, they are riven with imperfections. The interesting historical question is why US-style patent systems with all their imperfections have come to dominate other methods of encouraging inventive activity. The essays in the book suggest that the creation of a tradable but temporary property right facilitates the transfer of technological knowledge and thus fosters a highly productive decentralized ecology of inventors and firms
May 2021
Keywords: Immaterialgüterrechte / (DE-627)091366615 / (DE-2867)18176-1; Innovation / (DE-627)091367840 / (DE-2867)10459-1; Patent / (DE-627)09138253X / (DE-2867)10478-4; Patentrecht / (DE-627)091382548 / (DE-2867)10481-1; Geschichte / (DE-627)09136311X / (DE-2867)15690-2; Welt / (DE-627)09140004X / (DE-2867)16809-5; USA / (DE-627)091396867 / (DE-2867)17829-1